2021
DOI: 10.3390/su13137321
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Economical and Technological Analysis of MQL-Assisted Machining of Al-Mg-Zr Alloy Using PCD Tool

Abstract: Clean technological machining operations can improve traditional methods’ environmental, economic, and technical viability, resulting in sustainability, compatibility, and human-centered machining. This, this work focuses on sustainable machining of Al-Mg-Zr alloy with minimum quantity lubricant (MQL)-assisted machining using a polycrystalline diamond (PCD) tool. The effect of various process parameters on the surface roughness and cutting temperature were analyzed. The Taguchi L25 orthogonal array-based exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 48 publications
2
6
1
Order By: Relevance
“…In contrast, for material removal rate, feed rate is moderately signifcant to induce a favorable rate of material removal. Tis result is consistent with the earlier research conducted by various researchers [68,69]. Te R 2 value of 93.01% obtained for the MMR model provides evidence of its statistical signifcance.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, for material removal rate, feed rate is moderately signifcant to induce a favorable rate of material removal. Tis result is consistent with the earlier research conducted by various researchers [68,69]. Te R 2 value of 93.01% obtained for the MMR model provides evidence of its statistical signifcance.…”
Section: Resultssupporting
confidence: 92%
“…For surface roughness, it is clearly showing that the optimal level for turning is at the frst level of cutting speed, feed rate, and depth of cut. Specifcally, this means that the cutting speed at 119 m/min, feed rate at 0.11 mm/rev, and the depth of cut at 0.2 mm are the optimum values of cutting parameters for lowest surface roughens, which is in slight contrast with the results found by Karim et al [69]. However, Figure 6 plot for the S/N ratio indicates that there is less variance for changes in cutting speed, whereas there is greater variation for changes in feed.…”
Section: Resultscontrasting
confidence: 70%
“…Results revealed that MQL reduces carbon emissions and energy expenditure significantly by 9%–24% and 9%–27%, respectively, compared to dry machining. Similarly, Karim et al (2021) performed a sustainability study using a bottom-up approach during MQL machining of Al-Mg-Zr alloy. The findings demonstrated that MQL machining required relatively less cutting fluid, resulting in a decreased carbon footprint.…”
Section: Minimum Quantity Lubrication Machining Performancementioning
confidence: 99%
“…Khanna et al [22] evaluated the sustainability of conventional flood machining, cryogenic machining, and minimum quantity lubrication while machining Ti6Al4V and found cryogenic machining to be the most sustainable. Karim et al [23] evaluated the sustainability of MQL machining Al-based alloy using the PCD tool by evaluating environmental, economic and machining performance. MQL application consumed less energy and achieved higher metal removal with lesser tool changes.…”
Section: Introductionmentioning
confidence: 99%